Prognostic significance of cell cycle-associated proteins p16, pRB, cyclin D1 and p53 in resected oropharyngeal carcinoma - Michaela Plath; Martina A. Broglie; Diana Förbs; Sandro J. Stoeckli; Wolfram Jochum (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Human papillomavirus (HPV)-related oropharyngeal squamous cell carcinoma (OPSCC) has an improved outcome and may allow for treatment de-escalation. High-risk HPV (HR-HPV) infection is associated with deregulated expression of the cell cycle-associated proteins p16INK4, pRB, cyclin D1 and p53. The objective of this study was to assess cell cycle proteins as potential surrogate markers for HR-HPV DNA testing to identify OPSCC with favorable prognosis after resection. Methods Tissue microarray cores of 313 surgically treated OPSCC were stained for p16INK4a, pRB, cyclin D1 and p53 using immunohistochemistry. Protein expression was scored as high or low based on the proportion of positive carcinoma cells. Tumor samples were analysed for HR-HPV DNA with polymerase chain reaction-based testing. Associations between cell cycle protein expression and HR-HPV DNA status were evaluated by calculating sensitivity, specificity, predictive values, and diagnostic odds ratios (DOR). Kaplan-Meier and Cox regression analysis were applied to evaluate associations between cell cycle protein expression and patient outcome. Results High expression of p16INK4a, cyclin D1, pRB and p53 in tumor cells were observed in 51.8%, 51.4%, 41.9% and 33.5% of OPSCC, respectively. HR-HPV DNA positive were 158/313 (50.5%) tumor samples (HPV16: 147, HPV18: 1, HPV33: 5, HPV35: 2, HPV56: 2, and HPV59: 1). P16INK4a showed a higher DOR to predict HR-HPV DNA positivity than pRB, cyclin D1 and p53. Both the p16INK4a/pRB and the p16INK4a/pRB/cyclin D1/p53 signatures had lower DOR than p16INK4a alone. Improved 5-year overall and disease-specific survival were associated with HR-HPV DNA positivity, high p16INK4a, low pRB, low cyclin D1, and low p53 expression. Associations with improved outcome were also observed for the marker combinations high p16INK4a/positive HR-HPV DNA, high p16INK4a/low pRB and high p16INK4a/low pRB/low cyclin D1/low p53. In a multivariate analysis adjusted for age, smoking history, pT and pN category, high p16INK4a expression showed the lowest hazard ratio for death. Conclusions High p16INK4a expression is a reliable marker for survival prognostication in surgically treated OPSCC patients. Protein signatures including the pRB, cyclin D1 and p53 proteins do not further increase the prognostic performance of p16INK4a as a single marker.